Probiotic effect of a strain of Wickerhamomyces anomalus on fattening broilers - Garc?a, Yaneisy; P?rez, Mairiulys; Garc?a, Yanelis; Rodr?guez, B?rbara; Bocourt, Ram?n; Torres, Verena; Albelo, Nereyda; N??ez, Odalys; Guzm?n, Juan Alberto; Febles, Milagro; Noda, Aida C. (Cuban Journal of Agricultural Science, 2014)
In order to evaluate the probiotic type effect of a strain of Wickerhamomyces anomalus on some physiological and productive indicators of fattening broilers, a completely randomized design was used, and two groups of animals were established, with a hundred of broilers each. The first group had a basal diet of corn and soy, and the second had a basal diet with the addition of a strain of W. anomalus LV-6, with a concentration of 108 cfu/g of food. By including this yeast into the diet, an increase of the relative weight of the caeca (4.38 vs. 5.19 g/kg of liveweight, P < 0.05) and of the carcass (53.81 vs 56.12 %) (P < 0.01) and breast yield (24.86 vs 27.05 %, P < 0. 001) was confirmed, as well as the good health of the animals and the improvement of the response to vaccines (P < 0.05). It can be concluded that the addition of W. anomalus LV-6 to the diet of broilers provokes a probiotic response on the behavior of some physiological and productive indicators of the animals. Key words: yeast, probiotic activity, microbial additive, animal production